P150 Increased risk of ibd flare after sars-cov-2 infection. who's the more guilty: viral infection or therapy withdrawal?. (21st January 2022) - Bezzio, C; Guarino, A D; Fiorino, G; Armuzzi, A; Ribaldone, D G; Furfaro, F; Pugliese, D; Vernero, M; Variola, A; Gerardi, V; Scucchi, L; Viganò, C; et al.
Abstract: Background: In the last year, the severe adult respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic has spread rapidly around the world. The interactions between SARS-CoV-2 and inflammatory bowel disease (IBD) are so far not fully understood. In particular, no studies evaluated the potential role of SARS-CoV-2 on IBD course. Indeed, it is known that viral infections can be act as triggers for IBD flare and it is reasonable that the possible drug discontinuation during SARS-CoV-2 infection could in turn lead to an IBD flare. Methods: This was a prospective, observational case-control study. From March 11 th 2020 to June 30 th 2020 we enrolled IBD patients with proven SARS-Cov-2 infection ("cases") and IBD patients without SARS-CoV-2 infection matched for sex, age, diagnosis, therapy and clinical activity ("controls"). Cases and controls were followed-up at least for 6 months. Differences between case and control group were tested for significance using the Student's t test and Fisher's test, as appropriate. A two-tailed p value < 0.05 was indicative of statistical significance. Results: 219 IBD patients (127 UC, 58.0%) with SARS-CoV-2 infection and 219 IBD patients without SARS-CoV-2 infection were enrolled. Table 1 shows baseline features of the population. Among the 122 cases in clinical remission at the time of viral infection, 28 (22.9%) showed a disease flare; this percentage was significantly higher than that observed in controls: 12/137 (8.8%)(p=0.0018). Among patients with disease flare, there were no significant differences between cases and controls group in terms of age (42.3 ± 16.0 vs. 43.1 ± 15.4 years, p=0.44), gender (female 45.7% vs. 48.2%, p= 0.54), use of biologic therapies (p=0.83) and UC or CD diagnosis (p=0.06). Biologic therapy was temporary withdrawn more significantly in cases than in controls (68/202, 33.6% vs. 14/204, 6.9%) (p<0.001) and overall biologic therapy discontinuation was significantly associated with disease flare (OR 2.56, 95% CI 1.02–6.41, p=0.04). Conclusion: IBD patients with SARS-CoV-2 infection have an increased risk to have a clinical recurrence in short-term in comparison with IBD patients without SARS-CoV-2 infection. This increased risk could be due to the viral infection and/or to the temporary discontinuation of biologic therapies, because of infection.